Investments in Religious Capital: An explorative case study of Australian Buddhists - Barker, Michelle (Journal of global buddhism, 2007)
Since Buddhism became Australia’s fastest growing religion in 1996, the number of adherents has continued to increase dramatically. While there is much acceptance of this in Australia’s multicultural milieu, the effects of this growth are unclear. The concept of religious capital is now being used to understand some effects of religious practice, and is developed further as a way of understanding the broader societal effects of a religion. Expressions of Buddhist religious capital in Australia are documented and placed within a framework that identifies different types of religious capital to improve understanding of both the concept of religious capital and the effects of the ongoing growth of Buddhism in Australia.